The Implementation of DHCP Relay Using Pox Controller on Openflow Protocol - Ahmad Zaki Hamidi, Eki; Ridlo Effendi, Mufid; Ismail, Nanang (International Journal of Engineering and Technology, 2018)
The fastest of development in a network which is longer more complex, it needed developing and managing efficiently. On a network which has more computer, it needed effectivity of regulation of IP with DHCP server, many more of a subnet, has become DHCP Relay to be a solution. DHCP relay or agent relay is a protocol Bootstrap which is DHCP asks to have a message between client and server for DHCP to the different network. Software Defined Network (SDN) offers a new paradigm in network design, manage, and implementation, especially to support a needed and innovation in this case, which is longer more complex..Â